POSHAN’s abstract digest on maternal and child nutrition research - Issue 38 - Avula, Rasmi (International Food Policy Research Institute, 2021)
Issue 38 of the Abstract Digest brings to you a series of studies on nutrition outcomes, including prevalence of stunting and its association with women’s empowerment, nutrients in complementary feeding, and the impact of nutritional interventions among lactating mothers. In this issue we have also included two special sections. One features COVID-19 related studies and blogs, and the other features studies that have used the recently released National Family Health Survey-5 data.